Macrothrombocytic Thrombopathia. Clinical, Coagulation and Hereditary Aspects - Kańska, Barbara; Niewiarowski, S; Ostrowski, L; Popławski, A; Prokopowicz, J (Thrombosis and Haemostasis, 1963)
Macrothrombocytic thrombopathia (la dystrophie thrombocytaire hémorragipare congénitale) has been diagnosed in two sisters (10 and 12 years old) born of a consanguineous marriage. A short description of the clinical course in both patients is given. Microscopic examinations of stained blood smears revealed an abnormal size of platelets, the diameter of 80 per cent of platelets was greater than 4.3 ì. The platelet count in both children was normal except the period of haemorrhagic crises. The prolongation of bleeding time and defective prothrombin consumption were the only abnormalities found by means of routine coagulation study. Plasma clotting factors were normal. Platelets were lacking factor 1 and 3 but platelets agglutination, viscous metamorphosis and clot retraction were normal. Two forms of macrothrombocytic thrombopathia were ascertained in the patients family (17 members) by means of microscopic and coagulation studies. The first form (homozygous state) is a platelet anomaly associated with defective prothrombin consumption and bleeding tendency. The second one (heterozygous state) consists in platelet anomaly only. The authors suggest that macrothrombocytic thrombopathia is transmitted as an autosomic and incompletely recessive trait, some abnormalities being detected in heterozygotes. It was suggested that the microscopic examination of platelets in stained blood smears offers the possibilty for detection of heterozygotes.The pathogenesis and the mechanism of hemostatic defect of macrothrombocytic thrombopathia is briefly discussed.